Effect of deposition technique of Ni on the perpendicular magnetic anisotropy in Co/Ni multilayers - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
The perpendicular magnetic anisotropy (PMA) of Si/Pt 3.5/(Co 0.3/Ni 0.6)(n) /Cu 0.3/ Pt 3 (all thicknesses are rim) multilayers were investigated for two different sample sets by using ferromagnetic resonance (FMR) and magnetooptic Kerr effect (MOKE) techniques. In the first sample set all layers (buffer, cap, Co and Ni) were grown by magnetron sputtering technique while in the second sample set Ni sub-layers were grown by molecular beam epitaxy (MBE) at high vacuum. Apart from deposition technique of Ni, all other parameters like thicknesses and growth rates of each layers are same for both sample sets. Multilayers in these two sample sets display PMA in the as grown state until a certain value of bilayer repetition (n) and the strength of PMA decreases with increasing n. Magnetic easy axis's of the multilayered samples switched from film normal to the film plane when n is 9 and 5 for the first and second sample sets, respectively. The reason for that. PMA was decreased due to increasing roughness with increasing n. This was confirmed by X Ray Reflectivity (XRR) measurements for both sample sets. Moreover, in the first sample set coercive field values are smaller than the second sample set, which means magnetic anisotropy is lower than the latter one. This stronger PMA is arising due to existence of stronger Pt (111) and Co/Ni (111) textures in the second sample set. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Perpendicular magnetic anisotropy; Growth effect; Co/Ni multilayers; FMR